Surgical treatment of duodenal adenocarcinoma: ampullary vs. non-ampullary, short- and long-term outcomes - Tesarikova, Jana; Skalicky, Pavel; Kurfurstova, Daniela; Svebisova, Hana; Urban, Ondrej; Falt, Premysl; Zapletalova, Jana; Klos, Dusan; Lovecek, Martin (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2022)
BACKGROUND: The aim of this study was to evaluate symptoms, diagnostic methods, short- and long-term outcomes of surgical treatment in patients with duodenal adenocarcinoma. PATIENTS AND METHODS: A single center, retrospective, observational study of 52 consecutive patients with duodenal adenocarcinoma operated on with curative intent between 2006 - 2019. Duodenectomy as part of a hemipancreatoduodenectomy or total pancreatectomy procedure was performed for ADAC (ampullary duodenal/intestinal adenocarcinoma) or NADAC (non-ampullary duodenal adenocarcinoma). RESULTS: Prevailing symptoms were obstructive jaundice in the ADAC group (P<0.0001) and bleeding in the NADAC group (P=0.005), with larger tumor size in patients with NADAC (P=0.001). Complication rate, morbidity and mortality were comparable. Primary total pancreatoduodenectomy predominated in the NADAC group, 16.6% vs. 2.9%, and salvage completion pancreatectomy in the ADAC group, 6% vs. 0%. Significant prognostic factors for OS were perineural invasion (P=0.006) and adjuvant chemotherapy (P=0.045) in the ADAC group, and for DFS the total number of resected lymph nodes (P=0.042) and lymph node ratio (P=0.031) in the NADAC group. Median OS is 21 months and 5-year survival 27.3% in the NADAC group and 41.5 months and 52% in the ADAC group. CONCLUSION: Ampullary duodenal/intestinal adenocarcinomas are smaller than non-ampullary at diagnosis, with a higher rate of lymph node metastases, but with a better prognosis and long-term outcome in the presented cohort. Oral localisation of NADAC prevailed in the present cohort. Perineural invasion and postoperative oncological therapy are significant prognostic factors for OS in ADAC, but the total number of lymph nodes and lymph node ratio are significant prognostic factors for DFS in NADAC.
Keywords: Retrospective Studies; Prognosis; Ampulla of Vater; duodenal carcinoma; long-term survival; ampulla Vateri; nádory slinivky břišní; adenokarcinom; ampullary carcinoma; nádory ductus choledochus; nádory duodena; Neoplasm Staging; prognóza; retrospektivní studie; Humans; Pancreatic Neoplasms; Common Bile Duct Neoplasms; staging nádorů; outcomes; non-ampullary carcinoma; Adenocarcinoma; lidé; Duodenal Neoplasms